Perianeurysmal cerebral. Report of two cases - Sosa Albacete, Federico; Ayerbe , Jeremías; López Armaretti, Marianela; Zurrú, María Cristina; Baccanelli, Matteo (Revista Argentina de Neurocirugía, 2021)
Subarachnoid hemorrhage (SAH) secondary to aneurysmal rupture is an important cause of morbidity and mortality. There are many factors that increase the probability of rupture, the size, shape, location, incomplete endovascular exclusion of the aneurysm, among others. There are reports on perianeurysmal cerebral edema as a risk factor for aneurysmal rupture. Two cases are presented in the following article, both with right-sided sylvian aneurysm, associated with “perianeursmatic” edema.
Keywords: Edema; Aneurysm; Intracerebral; Intracranial Aneurysm; Perianeurysm; Subarachnoid Hemorrhage